Silk gland fi broinase: Case study in Bombyx mori and Samia cynthia ricini - Sumida, Motoyuki; Sutthikhum, Vallaya (Food Agricultural Sciences and Technology, 2016)
Fibroinase is a cathepsin L-like cysteine proteinase isolated from the silk glands of the silkworm, Bombyx mori, and the Eri silkworm, Samia cynthia ricini, and characterized by our research group. In B. mori, its physiological functions are disclosed as follows. (1) During each molt period in the larva, fi broinase is secreted into the lumen of the silk glands and digests the fi broin and sericin completely to make the lumen empty so that the silk gland cells can start synthesizing fi broin and sericin, and then secrete them into the lumen of the silk glands in the late molt period. (2) In day zero to day one pupa, fi broinase is secreted into the lumen of the silk glands and digests the remaining fi broin and sericin. (3) In the feeding period for each instar of the larva and in the spinning period for the last fi fth instar larva, fi broinase functions as a lysosomal proteinase in lysosomes within the silk gland cells for the digestion of obsolete proteins and organelles, such as mitochondria, endoplasmic reticulum, and ribosomal proteins, transported into the lysosomes for regeneration of the highly effi cient protein synthesis machinery. In S. cynthia ricini, the properties of fi boroinase are different in several points from those of B. mori, such as the N-terminal amino acid sequence, developmental profi le, and maximum activity. Higher maximum activity, 38 times the maximum activity of B. mori per individual insect, is observed at the end of spinning. The silk glands of S. cynthia ricini degenerate just after the end of the spinning and the day zero pupa has no silk glands. Accordingly, the physiological functions of fi broinase in S. cynthia ricini are the fi broinase functions (1) and (3) in B. mori. The purpose of this review article is to encourage researchers of insect science to start studying fi broinase of silk glands in other insect species and to fi nd out the species specifi city for a comprehensive view of silk gland fi broinase of a diverse array of insect species. As a guide for the study, we will present the study path in which knowledge of fi broinase in B. mori, and S. cynthia ricini, was obtained with the logic utilized.